Factors affecting consumption behaviour on men's skincare product / Fatin Syafiqah Taharen, Norashikin Ahmad Nawawi and Nur Syafikah Mohd Ariff - Taharen, Fatin Syafiqah; Nawawi, Norashikin Ahmad; Mohd Ariff, Nur Syafikah (2019)
Having healthy and beautiful skin is a step to confidence as the clarity of someone's skin is solely a helper in boosting confidence. In ancient ages, skincare products focused on taking care of women's beauty. Nowadays, male also wants the same steps to ensure skin's healthiness just as same as female does. This research aims to determine the factors that contribute consumption behaviours of men's skincare products. There are limited studies of the context found in Malaysia that solely focused in men's consumption behavior towards skincare products. With that, the findings of the effect of self-image, celebrity endorsement, social expectation and brand loyalty are among the factors that need to be identified which give the most contribution to the study. A questionnaire was distributed to men living in Malaysia with 138 respondents by using convenient sampling method. Logistic regression was used to test the model in SPSS version 22. Self-image, celebrity endorsement and brand loyalty were the factors mostly contributed to the study.